Design, arte e arquitetura: Eventos temporários na construção da cidade - Crispim, Samara Ferreira (2019)
In order to disseminate discussions related to contemporary design, the interdisciplinarity and the expansion of its field to the city scale, this work discusses, based on bibliographic research and the development of on-site analysis, the way design looks at art and architecture when designing new products and spatialities within the urban environment, based on the promotion of temporary events, proposing projects capable of promoting social change, behaving in a transverse way to envision other possibilities, links and perspectives of action and innovation.